Improved bactericidal efficacy and thermostability of Staphylococcus aureus-specific bacteriophage SA3821 by repeated sodium pyrophosphate challenges - Hyo Ju Choi (Nature Portfolio, 2021)
Abstract As antibiotic resistance is being a threat to public health worldwide, bacteriophages are re-highlighted as alternative antimicrobials to fight with pathogens. Various wild-type phages isolated from diverse sources have been tested, but potential mutant phages generated by genome engineering or random mutagenesis are drawing increasing attention. Here, we applied a chelating agent, sodium pyrophosphate, to the staphylococcal temperate Siphoviridae phage SA3821 to introduce random mutations. Through 30 sequential sodium pyrophosphate challenges and random selections, the suspected mutant phage SA3821M was isolated. SA3821M maintained an intact virion morphology, but exhibited better bactericidal activity against its host Staphylococcous aureus CCARM 3821 for up to 17 h and thermostability than its parent, SA3821. Sodium pyrophosphate-mediated mutations in SA3821M were absent in lysogenic development genes but concentrated (83.9%) in genes related to the phage tail, particularly in the tail tape measure protein, indicating that changes in the tail module might have been responsible for the altered traits. This intentional random mutagenesis through controlled treatments with sodium pyrophosphate could be applied to other phages as a simple but potent method to improve their traits as alternative antimicrobials.